Postural control of size of the feet of children in school age - Andrade, Daniela Fernanda Esteves De; Neves, Jessica Caroliny De Jesus; Fujisawa, Dirce Shizuko (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Postural control is the interaction between the systems, the central nervous and the musculoskeletal, based on information from the system somatosensory, vestibular and visual, to capture and control the body segments, alignments and movements. The studies reporting that data the anthropometric influence on the postural control, among the findings arte the characteristics of the feet, such as foot size and type. The gold standard instrument of evaluation of postural control is the force platform (PF). Objective: To determine the correlation between postural control and the length of the feet in students with eight years old. Method: Cross-sectional Study with convenience sample with students enrolled in schools of the city of Londrina/PR. The collection consisted of personal identification, anthropometric data, and assessment of postural control on the FP. The body mass was obtained by means of weighing on a digital scale, stature was measured using a tape measure and the length of the feet was measured by means of a tape measure positioned in the calcaneus until the end of the first finger. The evaluation of the postural control was in unipodal support, 30 seconds permanence, three attempts with one-minute interval between them. Results: We evaluated 346 school, 180 (52%) female and 166 (48%) were male. Leg preference was to the right on 224 (64.7%), and the median length of feet was of 0.21 (0.21/0.22) (m). The children presented themselves in the position one-leg area of the COP 13.41±6.77 (cm2 ). The correlation of COP with size of the feet has been identified, but considered to be low (p=0.000 and r= 0.224). Conclusion: The correlation between the postural control and the length of the feet was low, since the complex mechanism in which other intrinsic factors and extrinsic are also able to influence it.